Analyzing enablers of sustainable supply chain: ISM and fuzzy AHP approach. (14th August 2017) - Kumar, Divesh; Rahman, Zillur
Abstract : Purpose: This paper aims to intend to help focal firms which are keen to develop a sustainable supply chain by identifying enablers, in knowing the interrelationships involved and in ranking the enablers. Design/methodology/approach: Interpretive structural modeling and fuzzy MICMAC were used for the modeling and clustering of the enablers and fuzzy analytical hierarchy process has been used for the ranking purpose. Findings: Awareness about sustainability incentives, pressure from stakeholders, support from supply chain partners and demand from customer for sustainable products were found very important for developing a sustainable supply chain. Research limitations/implications: This research will help practitioners to appreciate the importance of the enablers to focus on the making sustainability adoption feasible across the supply chain. This would also facilitate focal firm management to develop a sustainability culture across the supply chain. Originality/value: Similar work has not been carried before in which interaction among enablers and their priorities were analyzed using hybrid methodologies in developing country context.